Students’ Perception and Engagement in English Project-Based Learning: A Qualitative Study at Senior High School Level - Irham, Muhammad; Mahmud, Murni; Baa, Sultan (Universitas Negeri Makassar, 2025)
This qualitative study explores students’ perceptions and engagement in the implementation of Project-Based Learning (PjBL) in English language classrooms at the senior high school level. The research focuses on uncovering how students perceive the use of PjBL, what aspects enhance their motivation and involvement—such as group collaboration, use of technology, and creativity—and what challenges they encounter, including time management, task division, and language comprehension. Five students from SMA Negeri 9 Wajo participated in in-depth interviews to share their experiences, while observations provided additional insight into classroom dynamics. The findings reveal that students generally hold positive perceptions toward PjBL, highlighting increased enthusiasm, improved English skills—especially in speaking, writing, and vocabulary—and a greater sense of ownership over their learning. Collaborative projects and authentic tasks were cited as key motivators, though students also expressed concerns about unequal participation and limited time for project completion. The study emphasizes the importance of student voice in evaluating educational strategies and offers practical suggestions from students to improve future PjBL activities.